Connectedness is in my character: the relationship between nature relatedness and character strengths. Issue 12 (1st December 2020) - Merino, Amparo; Valor, Carmen; Redondo, Raquel
Abstract: Fostering interdependence with nature is a central goal of environmental education. Exposing students to nature has been a common practice in environmental education for nurturing this connection among students. However, this exposition is not always feasible, especially in the context of higher education, nor is it clear that exposure to nature engenders nature connectedness equally among students. Thus, there are calls for a greater understanding of the psychological factors that may impinge on greater nature relatedness so to identify complementary educational routes for nurturing this interdependent construal. Responding to these calls, in a sample of 967 students, we examine whether character strengths covariate with nature relatedness and which character strengths better differentiate between high and low levels of nature relatedness. Our results show that intellectual character strengths (i.e. appreciation of beauty, love of learning, and curiosity) are strongly associated with nature relatedness. Moreover, our findings show that appreciation of beauty is the strongest covariate of nature relatedness. These findings have theoretical and practical implications for environmental education.